Study on Marine Ecological Environment Quality Level in Liaoning Province - LIU Yang; XIA Na; LIU Chen; KANG Jia (Haiyang Kaifa yu guanli)
This study focuses on Liaoning Province as the research subject, selects relevant data from 2011 to 2020, constructs an evaluation index system for the development of the marine ecological environment in Liaoning Province, and utilizes the entropy method to comprehensively assess the level of marine ecological development in Liaoning Province over the past decade. The findings indicate that the quality of the marine ecological environment in Liaoning Province exhibited a trend of rapid decline, fluctuating decline, and then fluctuating increase from 2011 to 2020. In terms of classification indices, the marine resource endowment level in Liaoning Province experienced a sharp decline followed by annual increases during this period. The level of marine environmental quality demonstrated a wavy developmental trend. The marine restoration system showed a pattern of initial decrease followed by an increase, remaining relatively stable. The trend in marine social development levels displayed a wave-like developmental pattern opposite to that observed for marine environmental quality.